"Liquid, gel and soft glass" phase transitions and rheology of nanocrystalline cellulose suspensions as a function of concentration and salinity. Issue 10 (26th February 2018) - Xu, Yuan; Atrens, Aleks D.; Stokes, Jason R.
Abstract : Rheological methods reveal a continuous transition between microstructure states of nanocellulose colloidal rod suspensions. Abstract : The colloidal size and rod morphology of nanocrystalline cellulose (NCC) lead to suspensions with useful phase and gelation behaviours as well as complex rheologies. However, these have not been comprehensively evaluated previously. Here we report the detailed phase behaviour of sulphonated NCC aqueous suspensions as a function of concentration and salinity. Four phases – liquid, viscoelastic, repulsive glass and attractive glass/gel – are identified in terms of their distinct rheological behaviours. The liquid–solid transitions (LSTs) are determined rheologically, and these are supported by a simplified model based on the DLVO theory that indicates the importance of charge in determining the phase behaviour. Rheology is also used to investigate the solid–solid transition from a repulsive glass to an attractive gel with increasing salt at high NCC concentrations. A time-dependent aging phenomenon is observed in suspensions with a composition just below the LSTs, and the implications of this on the dynamics occurring during gelation processes are discussed. This work can be directly applied to the development of structure–function relationships and the expanding utilisation of NCC suspensions, whilst also providing a basis for the study of charged colloidal rods more generally and evaluation of theoretical models.